2014
DOI: 10.1111/jnp.12061
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism, executive control, and age at diagnosis among people with early‐stage Alzheimer's disease in Wales

Abstract: The observation of a bilingual advantage in executive control tasks involving inhibition and management of response conflict suggests that being bilingual might contribute to increased cognitive reserve. In support of this, recent evidence indicates that bilinguals develop Alzheimer's disease (AD) later than monolinguals, and may retain an advantage in performance on executive control tasks. We compared age at the time of receiving an AD diagnosis in bilingual Welsh/English speakers (n = 37) and monolingual En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 60 publications
0
49
2
3
Order By: Relevance
“…It is, however, not always the bilingual group that consists of immigrants. In a recent study by Clare et al (2014), which found no evidence for a delaying effect of bilingualism on the onset of Alzheimer's Disease, many monolinguals were people who migrated to Wales from other parts of the country, while the bilingual group consisted mainly of autochthonous population.…”
Section: The Importance Of Confounding Variablesmentioning
confidence: 94%
“…It is, however, not always the bilingual group that consists of immigrants. In a recent study by Clare et al (2014), which found no evidence for a delaying effect of bilingualism on the onset of Alzheimer's Disease, many monolinguals were people who migrated to Wales from other parts of the country, while the bilingual group consisted mainly of autochthonous population.…”
Section: The Importance Of Confounding Variablesmentioning
confidence: 94%
“…Fourth, this study was restricted to idiopathic AD patients, and excluded familial AD patients who have a distinctly earlier onset of symptoms. Lastly, some studies used the age at diagnosis of AD to evaluate the onset age [5, 6], but this method was not suitable for Chinese AD patients because some of them, especially those with low education levels or living in the countryside, waited for several years before being seen by a physician, and were then diagnosed with moderate or severe AD. Accordingly, the age at onset of symptoms of AD was used in our study in accordance with the studies by Craik et al [1] and Alladi et al [2].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, more Alzheimer’s disease (AD) associated brain atrophy is seen in bilinguals relative to monolingual controls, suggesting that bilinguals maintain a similar level of cognitive performance despite a greater degree of underlying AD pathology [20]. Nevertheless, other studies have failed to replicate these findings [2126]. …”
Section: Introductionmentioning
confidence: 99%